Obligatory Insurance as a Form of Social Engineering: A Comparison Paper Between the United States, Italy, Aruba and Poland - Heller, Thomas Allan; Rigoldi, Silvia; Burgos, Jessica; Sasinowski, Mateusz (Collected Papers of Thomas A. Heller, 2025)
Insurance has been around for centuries. Traditionally, it has been purchased to protect the purchaser, namely, the insured. Over time, the insurance industry has developed an increasing number of products, so that at present one can purchase insurance to cover nearly every risk imaginable. The concept of mandatory or obligatory insurance is a fairly recent development. It traces its origins to the widespread use of the motor vehicle and also employment. Obligatory insurance is designed to protect certain classes of persons, such as workers and those who sustain injury and damage at the hands of others. In this article, the authors compare the current state of obligatory insurance in four democratic countries: the United States, Italy, Aruba and Poland. The aim of the article is to catalogue the similarities and differences in obligatory insurance in those four countries. The countries studied all have obligatory insurance designed to offer some degree of protection to workers injured on the job, and in the course and scope of their work, and to those involved in vehicular collisions. The other primary takeaway from our research is that, predictably, there is less obligatory insurance in the United States than in the other countries studied.